Pengaruh Motivasi Belajar dan Penggunaan Media Power Point terhadap Hasil Belajar Mata Pelajaran Bahasa Indosesia - Wulan, Werdining (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
This research is a causal study (correlation) with 33 students of class IX in the odd semester of the 2014–2015 academic year at Al Muttaqin Middle School, Kec. Patrang Jember. The following are the findings of this study: (1) Powerpoint media and learning motivation affect the learning achievement of class IX students of SMP Al Muttaqin because Fcount (14.529) > Ftable (3.32) and its significance value is 0.000. Considering that the coefficient of multiple determination (R2) is 0.492 (49.2%) and is influenced by other variables of 50.8%, the influence of PowerPoint media and learning motivation on improving student achievement is not too significant. (2) The importance of student motivation in determining academic success.